The Recuperation of Climate Engagement: A Dispositif Analysis of the Carbon-Tracking App OneClimate - Gaßner, Christoph; Slunecko, Thomas (International Review of Theoretical Psychologies, 2026)
Many of the most pressing issues of our time are consequences of the way our global economy is organized. As such they call for forms of collective engagement that transcend the level of individual efforts. However, many political imperatives addressing these problems are directed at the individual: Reduce your carbon footprint! Practice social distancing! Such imperatives undermine collective efforts by undercutting the search for a collective response with a direct call for individual action. Theoreticians like Slavoj Žižek or Shoshana Zuboff have pointed to capitalism’s self-enhancing tendencies to appropriate resistive impulses as market opportunities. Current digital capitalism’s appropriation strategies often connect to individualistic imperatives, and smartphone applications have become essential vectors in this. Carbon tracking apps, for example, are enticing individuals to cut down on carbon emissions by measuring their carbon footprint. We analyse one such carbon tracking app, OneClimate, by systematically stepping through its interface. Such walkthrough creates a data basis of screenshots and field notes that allows for a reconstruction of the app’s structure and functions, the intended use, and the ideal user. Our analysis then exposes the app as a micro-dispositif, i.e., as a sociocultural artefact that aligns the self-governance of individuals with the requirements of neoliberal governance. While providing us with practical means for individual little action for the better, it pushes aside the felt need for system-challenging collective engagement and theorising. Through this offering of a quiet conscience, our empathy with Gaia, our capacity to mourn its destruction and to feel guilty and ashamed for being part of it, is hijacked, reoriented towards the status quo, and further capitalized on.